Human Rights and Disability Advocacy - Maya Sabatello, Marianne Schulze (University of Pennsylvania Press, 2013)
Th e UN Convention on the Rights of Persons with Disabilities came into force on Saturday 3 May 2008, thirty days aft er the twentieth nation had deposited its documents of ratifi cation with the United Nations (Article 45(1)). It had taken relatively little time for twenty countries to ratify the CRPD since it was opened for signing in March 2007, and remarkably, when France deposited its document of ratifi cation in February 2010, it became the eightieth nation to do so. Th e CRPD takes a rather modern and pragmatic approach to the rights of us persons with disabilities. First, Article 3 sets forth eight key principles, including nondiscrimination and equality, with my favorite principle being inherent dignity. Second, as well as including civil and po liti cal rights, it also encompasses economic, social, and cultural rights. Th us, the rights to adequate health information and care and education come squarely within the scope of the CRPD. Th ird, the special plight of women and children with disabilities are recognized in Articles 6 and 7 of the CRPD. In other words, as well as having the burden of disability, women and children are also discriminated on the grounds of sex or age. Finally, although Article 35 requires states parties to periodically report in much the same way as do the other UN treaty bodies, the CRPD goes farther by requiring them to establish a domestic body to both monitor and implement the CRPD. Under Article 33, as well as erecting one or more focal points in government, states parties are required to establish a framework to monitor and implement the CRPD. Th is framework may contain human rights agencies, but two other groups must be represented. Th ey are disabled peopleâ€™s organizations and persons with disabilities acting in their individual capacities. In a book of this nature, it is not for its preface to chart the history of the CRPD. However, it is essential to appreciate that the â€œmovers and shakersâ€ for the CRPD were civil society, that is, DPOs and persons with disabilities. Without the expertise and pressure from civil society that changed the minds of many governments, I venture to conclude that we would not have this convention at the present time.